FENOMENA PESERTA DIDIK DAN PROBLEM KESEHATAN MENTAL DI ERA DIGITAL: SUATU REFLEKSI BAGI PERADABAN DUNIA PENDIDIKAN - Ani Sukaisih; Sayid Ahmad Ramadhan (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
The purpose of the study is to know and describe the phenomenon of students and health problems in the digital era. Literature studies are used as a type of research with results presented descriptively. The results showed that: The phenomenon of students is focused on addiction to using smartphones, delinquency due to promiscuity, lack of reading literacy (offline and online), bad speech, display and use Eastern and Westernized styles of dress or appearance but are not in line with religious shari'a and societal norms, and loss of respect for parents or educators or teachers. The mental health problems in the digital era are influenced by two domains (internal and external) namely the lack of ability to process, manage and show emotional feelings according to their place, often experiencing turmoil due to love, friendship and family problems, Experiencing a decrease in critical thinking skills due to being spoiled by technological sophistication, Less open to problems and experiencing pressure has implications for depression or stress (mild and/severe). Then for efforts to respond to it, it is supported by three aspects (family, school and community) through giving advice and punishment according to fairness, establishing cooperation between all layers determining the success of the educational process and having an attitude of openness to students